Managing communications challenges in requirement elicitation - Che Pa, Noraini; Mohd Zin, Abdullah (Springer, 2011)
Eliciting requirements for a system is an important activity in requirement engineering. This process involves communication between customers and developers. Researchers have identified that poor communication is one of the most common problems in identifying and defining customer’s requirements. Managing communication is challenging and difficult as this process also includes cognitive aspect, personalities, techniques and tools. An study was carried out to explore the communication challenges that are faced by developers and customers during software requirement elicitation in Malaysia. The results of this study had shown that there are some important communication challenges during software requirements elicitation process in Malaysia. In addition, most of the practitioners were pursuing the practices that have been traditionally used by the organizations. Consequently, the results of this study have given us a good incentive to expand our research in the area of software requirements elicitation.